Radiation sterilization of Mexican fruit fly Anastrepha ludens (Leow) based on pupal eye color - Resilva, Sotero S.; Hernandez, Emilio; Obra, Glenda B. (2019)
This paper reports on the documented pupal eye color changes of Mexican fruit fly Anastrepha ludens (Leow) at different holding temperatures. In holding mature larval samples at 15, 19, and 26ºC (standard holding temperature); 28ºC; and at environmental temperature (24?34ºC), the development of pupae lasted 49, 33, 16, 15, and 16d, respectively. Holding pupae at lower temperature delays pupal development and slows down progression of eye color changes. This is very important in manipulating pupal development, especially when uncontrolled problems occur during sterile insect technique (SIT) operations. The recommended timing of pupal irradiation for A. ludens at 26ºC (standard holding temperature) is 2d before adult emergence, where the pupae are 12?14d old and the eye colors are dark brown, very dark brown, and dark grayish green. Using this eye colors as the reference guide for irradiation of pupae, the right age when held at 15, 19, and 28ºC and at environmental temperature (24?34ºC) was 41?45, 28?31, 11?13, and 12?14d old, respectively. A table using documented and close-up photograph of pupal eye color can be used as a reference guide to determine the best time for the irradiation of pupae in an SIT program. (Author's abstract)